Legal Consequences of Depriving Women of Education in Afghanistan - Najiba Farahmand (Fakultas Hukum Universitas Islam Indonesia, 2026)
The denial of women’s right to education in Afghanistan, especially after the Taliban returned to power in 2021, is considered one of the most serious human rights violations. The right to education is recognized as a fundamental human right in international documents such as the Universal Declaration of Human Rights, the Covenant on Economic, Social and Cultural Rights, and the Convention on the Elimination of All Forms of Discrimination against Women. Despite these commitments, the Taliban have deprived millions of Afghan women and girls of this fundamental right by banning girls’ education beyond the sixth grade and closing universities. This research aims to examine the legal consequences of women’s lack of access to education in Afghanistan. The research method in this article is descriptive-analytical, and the information was collected through library resources, international law documents, and relevant reports of international organizations. The research findings show that, in addition to violating the right to education, women’s deprivation of education leads to violations of human dignity, reduced political and social participation of women, limited job opportunities, and increased social injustice. The research concludes that the international community and international institutions have an important responsibility to support the right to education of Afghan women and must provide access to education for Afghan women and girls through diplomatic pressure, human rights monitoring, and the creation of alternative educational opportunities.